Tick-Borne Encephalitis Virus and Borrelia burgdorferi Seroprevalence in Balkan Tick-Infested Individuals: A Two-Centre Study - Jakimovski, Dejan; Mateska, Sofija; Dimitrova, Emilija; Bosilkovski, Mile; Mijatović, Dragana; Simin, Verica; Bogdan, Ivana; Grujić, Jasmina; Budakov-Obradović, Zorana; Meletis, Eleftherios; Kostoulas, Polychronis; Cabezas-Cruz, Alejandro; et al. (MDPI AG, 2023)
Lyme borreliosis (LB) and tick-borne encephalitis (TBE) are important tick-borne diseases in Europe. This study aimed to investigate the seroreactivity against Borrelia burgdorferi and TBE virus (TBEV) in tick-infested individuals in North Macedonia and Serbia. Serum samples were collected from tick-infested individuals and from healthy individuals in the same regions. Samples were tested for anti-Borrelia IgG reactivity and TBEV-neutralizing antibodies. Results showed higher seroreactivity against Borrelia antigens in patients and healthy donors from Novi Sad compared to those from the Skopje region. However, there was no statistically significant difference between tick-infested patients and healthy donors within each region. No TBEV-neutralizing antibodies were detected in participants from Novi Sad or in the control groups, except for one person from North Macedonia who had a moderate TBEV-neutralizing reaction. The study highlights the need for improved surveillance and diagnostic capabilities for LB and TBE in these regions. It also suggests the potential existence of TBEV foci in North Macedonia. The findings provide a complementary understanding of the LB and TBE epidemiology in the studied regions; however, further research is needed to investigate the presence and distribution of Borrelia spp. and TBEV in ticks to assess the significance of detected seroreactivity.